Thermal oscillations provoke physiological and biochemical changes on wheat plants infected by Pyricularia oryzae - Silva, Bruno do Nascimento (Universidade Federal de Viçosa, 2019)
Wheat blast, caused by Pyricularia oryzae, is the most important wheat disease nowadays. High temperatures, as a consequence of climatic changes, can potentially cause physiological and biochemical changes on plants by altering their resistance to diseases. This study aimed to determine whether thermal oscillations could cause physiological and biochemical changes on wheat plants when infected with P. oryzae. Plants were submitted to different thermal acclimations (19°C and 28°C) for five days before being inoculated with P. oryzae. After inoculation, plants were kept at 25°C for 24 h and then either transferred to the initial temperature conditions or transferred to different temperature combinations (19oC→28°C and 28°C→19°C) during three days. Non-inoculated plants were submitted to these same conditions. Blast development was reduced on plants submitted to thermal acclimatization of 19oC→19oC compared to plants exposed to 28°C→28°C. There was no significant difference for blast severity between the thermal acclimations of 19oC→28°C and 28°C→19°C. Plants submitted to 28°C before or after inoculation showed impairments on photosynthesis with lower values for maximum photosystem PSII photochemical efficiency and effective PSII quantum yield, but high values for quantum yield of non-regulated energy dissipation besides lower concentration of pigments, reduction on stomatal conductance and an increase in the internal CO 2 concentration. There was high superoxide dismutase and lower ascorbate peroxidase activities for inoculated plants submitted to thermal acclimatization of 28°C→28°C. Low and high concentrations of superoxide anion and hydrogen peroxide, respectively, occurred for inoculated plants acclimated at 28°C→28°C. High chitinase, phenylalanine ammonia-lyase, and peroxidase activities occurred for inoculated plants acclimated at 28°C→28°C and 19°C→28°C. Polyphenoloxidase activity was lower for inoculated plants submitted to 28°C after or before fungal inoculation. Lipoxygenase increased on inoculated plants exposed at thermal acclimatization of 19oC→19oC. The malondialdehyde concentration was high for inoculated plants submitted to 28°C after or before fungal inoculation. In conclusion, blast development was favored on plants pre-acclimated at 28°C before fungal inoculation and kept at this same temperature during fungal infection process. By contrast, blast development was quite similar on plants pre-acclimated at 19 and 28°C before inoculation with P. oryzae and submitted, respectively, to temperatures of 28 or 19°C after inoculation. Wheat plants exposed at 28°C during the fungal infection process showed damage to the photosynthetic apparatus, a less efficient antioxidative system, and a minor contribution of the enzymes related to host defense. Key words: Defense enzymes. High temperatures. Host resistance. Photosynthesis. Wheat blast

A brusone do trigo, causada por Pyricularia oryzae, é a doença mais importante do trigo hoje em dia. As altas temperaturas, como consequência das mudanças climáticas, podem causar alterações fisiológicas e bioquímicas nas plantas, alterando sua resistência a doenças. Este estudo teve como objetivo determinar como as oscilações térmicas podem causar alterações fisiológicas e bioquímicas em plantas de trigo quando infectadas com P. oryzae. Plantas foram submetidas à diferentes aclimatações térmicas (19°C e 28°C) por cinco dias e inoculadas com P. oryzae. Após a inoculação, as plantas foram mantidas a 25°C durante 24 horas e depois transferidas para as condições iniciais de temperatura ou transferidas para diferentes combinações de temperatura (19°C→28°C e 28°C→19°C) durante três dias. Plantas não inoculadas também foram submetidas à essas mesmas condições. O desenvolvimento da brusone foi menor nas plantas submetidas à aclimatização térmica a 19°C→19°C em relação às plantas expostas a 28°C→28°C. Não houve diferença significativa para a severidade da brusone entre a aclimatação térmica de 19°C→28°C e 28°C→19°C. Plantas inoculadas submetidas a 28°C antes ou após a inoculação, apresentam prejuízos na fotossíntese com menores valores da máxima eficiência fotoquímica do PSII, rendimento quântico efetivo do PSII, mas maiores valores de rendimento quântico da dissipação de energia não regulada, além de menor concentração de pigmentos, redução da condutância estomática e aumento da concentração interna de CO2 . O metabolismo antioxidante foi alterado com maiores atividades de superóxido dismutase e menores de ascorbato peroxidase em plantas inoculadas e submetidas à aclimatização térmica a 28°C→28°C. Esses resultados estão diretamente relacionados com menores e maiores concentrações de ânion superóxido e peróxido de hidrogênio, ocorrendo respectivamente em plantas inoculadas e expostas à aclimatações térmicas 28°C→28°C. As maiores atividades de quitinase, fenilalanina amônia-liase e peroxidase ocorreram nas plantas inoculadas a 28°C→28°C e 19°C→28°C. A atividade da polifenoloxidase foi menor nas plantas inoculadas submetidas a 28°C antes ou após a inoculação do fungo. A atividade da lipoxigenase aumentou nas plantas de trigo inoculadas e expostas a aclimatização térmica a 19°C→19°C. A concentração de malondialdeído foi alta em plantas inoculadas submetidas a 28°C antes ou após a inoculação. Em conclusão, foi demonstrado que o desenvolvimento da brusone foi favorecido em plantas de trigo pré-aclimatadas a 28°C antes da inoculação com P. oryzae e mantidas nesta mesma temperatura durante o processo de infecção fúngica. Por outro lado, o desenvolvimento da brusone foi bastante similar em plantas pré-aclimatadas a 19 e 28°C antes da inoculação com P. oryzae e submetidas, respectivamente, a temperaturas de 28 ou 19°C após a inoculação. Plantas de trigo expostas a 28°C durante o processo de infecção fúngico apresentam prejuízos no aparelho fotossintético, um sistema antioxidante menos eficiente e uma pequena contribuição de enzimas relacionadas à defesa do hospedeiro. Palavras-chave: Enzimas de defesa. Altas temperaturas. Resistência do hospedeiro. Fotossíntese, Brusone do trigo
Oscilações térmicas provocam alterações fisiológicas e bioquímicas em plantas de trigo infectadas por Pyricularia oryzae
Keywords: Trigo - Resistência a doenças e pragas - Efeito da temperatura; Enzimas; Alta temperatura; Fotossíntese; Brusone; Fisiologia de Plantas Cultivadas